Early-stage investigators’ experiences with an National Institutes of Health Pilot Award Program - Cyleste C. Collins; Jacqueline Dolata; Elodie Nonguierma; Mona Shediac-Rizkallah; Ashwini R. Sehgal; J. Daryl Thornton (Journal of Clinical and Translational Science)
Abstract